2023
DOI: 10.3389/fpsyg.2023.1126815
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on emerging trends in the dynamic evolution of digital addiction and depression

Abstract: IntroductionUsing digital addiction as an umbrella term to cover any type of addictions to digital technologies such as the internet, smartphones, social media, or video games, the current study aimed to reveal the intellectual structure and evolution of research addressing digital addiction-depression relationship.MethodsThe study combined bibliometric and science mapping analysis methods for this purpose. Data for the study was gathered from Web of Science Core Collection after a comprehensive process of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 229 publications
0
8
0
Order By: Relevance
“…One final point we would like to make is bound up to social justice perspective. Research indicates that injustices resulting from the socio-economic, racial or cultural factors could seriously damage the academic achievement and well-being of students (Saunders, 2017), and the enactment of social justice leadership could help alleviate these negative outcomes (Karakose, Tülübaş, & Papadakis, 2023). From the perspective of digital transformation, technology-integrated education inextricably brings with it the problem of equity because students are often separated by the 'digital divide' resulting from gender, culture or economic injustices (Flanagan & Jacopsen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…One final point we would like to make is bound up to social justice perspective. Research indicates that injustices resulting from the socio-economic, racial or cultural factors could seriously damage the academic achievement and well-being of students (Saunders, 2017), and the enactment of social justice leadership could help alleviate these negative outcomes (Karakose, Tülübaş, & Papadakis, 2023). From the perspective of digital transformation, technology-integrated education inextricably brings with it the problem of equity because students are often separated by the 'digital divide' resulting from gender, culture or economic injustices (Flanagan & Jacopsen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As for the section regarding safety, lack knowledge in this aspect (Porlán & Sánchez, 2016;Gallego-Arrufat et al, 2019) is noticable both for teachers and students. Although the levels were adequate, the need for in-depth development after the pandemic era is still evident, and there is still room for improvement (Karakose, Tülübas ¸& Papadakis, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Problematic social media use can involve various categories of digital platforms that facilitate online interaction, communication, and content sharing [ 14 , 15 ]. The social media landscape is constantly evolving, particularly among teenagers, who tend to be at the forefront of these changes [ 16 ]. According to a recent survey by the Pew Research Center [ 17 ] focusing on American teenagers aged 13 to 17, TikTok has experienced a significant surge in popularity since its introduction to North America several years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies highlight various detrimental effects of social media on the mental health and overall well-being of people regardless of age [ 6 , 13 , 31 , 32 , 33 , 34 , 35 ]. Review studies and meta-analyses showed correlations between problematic social media use and heightened symptoms of depression, anxiety, stress, and decreased well-being [ 6 , 12 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], especially among adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation